A genome-wide scan for genes involved in primary vesicoureteric reflux. Issue 11 (27th July 2007) - Kelly, H; Molony, C M; Darlow, J M; Pirker, M E; Yoneda, A; Green, A J; Puri, P; Barton, D E
Abstract : Background: Vesicoureteric reflux (VUR) is the retrograde flow of urine from the bladder into the ureters. It is the most common urological anomaly in children, and a major cause of end-stage renal failure and hypertension in both children and adults. VUR is seen in approximately 1–2% of Caucasian newborns and is frequently familial. Objective and methods: In order to search for genetic loci involved in VUR, we performed a genome-wide linkage scan using 4710 single-nucleotide polymorphisms (SNPs) in 609 individuals from 129 Irish families with >1 affected member. Results: Nonparametric linkage (NPL) analysis of the dataset yielded moderately suggestive linkage at chromosome 2q37 (NPLmax  = 2.67, p<0.001). Analysis of a subset without any additional features, such as duplex kidneys, yielded a maximum NPL score of 4.1 (p = 0.001), reaching levels of genome-wide statistical significance. Suggestive linkage was also seen at 10q26 and 6q27, and there were several smaller peaks. Conclusion: Our results confirm the previous conclusion that VUR is genetically heterogeneous, and support the identification of several disease-associated regions indicated by smaller studies, as well as indicating new regions of interest for investigation.